The Characterization Of Clays From Latuhalat Village Activated Using Ammonium Nitrate - Latupeirissa, Jolantje; Fransina, Eirene G. (Indonesian Journal of Chemical Research, 2014)
Research on characterization clays from Latuhalat village before and after the activation using ammonium nitrate has been carried out. The brick was grinded, washed with aquadest and filtered. The clays was dried for 4 h in oven at 120Â°C, then it was soaked in HCl 1M for 30 min and was filtered. The clays in oven at 110Â°C for 5 h. The clays were sieved and activated using ammonium nitrate solution 700 ppm for 5 hours followed by filtration and heating in a furnace with temperature 5000C for 4 hours. The results of this research show that the adsorption of Pb2+ metal ions by ammonium nitrate salts, activated clays occur at pH 7 with 4 hours of contact time at concentrations of 100 ppm and heavy absorbent 0.15 g. Next clays are not activated NH4NO3 and activated NH4NO3 are characterized by SEM, FT-IR, and XRD. After the adsorption clays are characterized also by FT-IR. SEM micrograph with results on samples of clay before and after activated with magnification 10.000x showed a huge difference. Porosity clay before activation is relatively small compared to clay after activated. Sample after sample surface showed that activated the typical micro-structure is clearly visible in the shape of the flat, and slightly layered hexagonal. FT-IR analysis of clay before and after activation, activation and after adsorption showed the results did not very much. On clay prior to activation with NH4NO3 on the uptake about 900 cm-1 is the functional group montmorilonite. For the clays after adsorption showed the existence of ties between clay particles with metal. For metal uptake there are areas around 425 cm-1. The result analysis of x-ray diffraction of clays before and after activation of NH4NO3 indicates the result value of 2Î¸ in a row is 26,65470 and 26,87750 which is area with indication of quartz SiO2.